Early Marriage in the Light of Al-Qur'an and Hadith: Exploring its Impacts - Liddini, Laily (Qanun: Jurnal Hukum Keluarga Islam, 2024)
Early marriage in Banyumas is high, factors causing the high rate of underage marriage in Banyumas include economic factors to shift the burden, education factors, social media social media factors, and religious understanding factors. The purpose of this paper is to find out the causes and effects of early marriage and see from the perspective of the Qur'an and Hadith. The method used in this study is library research with a descriptive approach to analysis. The results of this study, the impact of early marriage include First: it tends to give birth to poor families and a weak generation due to lack of education. Second: dropping out of school has a bad future. Third: not having the ability to take care of the family because the mind is immature, and Fourth: impaired reproductive health. In Surah An-Nisa verse 9, there is a prohibition to leave behind a generation that is weak both logically and financially. As for the hadith, there is also a suggestion to create a financially strong generation. As for the hadith, there are several narrations that show the age of maturity of Sayidah 'Aisha in starting a household with the Messenger of Allah. Among them, first Sayidah Aisyah remembers the time her parents converted to Islam, this shows that she was born in the early days of prophethood, not after prophethood. Secondly, Sayidah 'Aisha along with um Sulaim helped in the battle of Uhud and the Battle of Badr, the Prophet forbade not allowing children who were not yet 15 years old, this shows that his age at the time of joining the war was 15 years. Third, Sayidah 'Aisyah and her sister are 10 years apart. When Asma' was between 27 and 28 years old in 1 AH, then Sayidah 'Aisha was between 17 and 18 years old in 1 AH. This counters the narration that shows Sayidah 'Aisyah married at the age of 6 years.